Realization of character in historical context: a comparative analysis of postmodern novels by H. Mantel, M. Bradbury and P. Ackroyd (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2024)
This article examines the realization of character traits within historical context conditions in postmodern novels, specifically analyzing how presentation methods of historical context influence character development across different genre frameworks. The study establishes that in historical novels following classical models, context serves as a personality-forming factor (H. Mantel), whereas in multi-genre postmodern novels, context either emerges as a simulacrum reality shaped by the character (M. Bradbury) or expands beyond textual boundaries to dominate the composition, thereby weakening its impact on character development (P. Ackroyd). The research explores character realization through literary devices including irony, internal commentary, semantic shifts in external utterances, and adaptive narrative strategies responding to situational contexts.
Keywords: historical context; character traits; postmodern novel; narrative strategies; Hilary Mantel; Malcolm Bradbury; Peter Ackroyd